A method for the measurement of mass and number of graphene oxide sheets in suspension based on non-spherical approximations. (2nd June 2021) - Crica, Livia Elena; Dennison, Thomas James; Guerini, Elise Andrea; Kostarelos, Kostas
Abstract: Currently, particle analysis of 2D materials in suspension is commonly restricted to microscopic techniques in the dry state, and thus does not permit an accurate investigation of colloidal suspensions. Colloids in bulk can be assessed by light scattering and diffraction to investigate features such as their hydrodynamic size, charge and concentration. However, the main drawback of such techniques lies in the application of analytical and computational methods based on models assuming particle sphericity which are not representative for 2D materials. Resonance mass measurement (RMM) is a technique which can enable the analysis of 2D materials in suspension without the assumptions of spherical models. Here, we report the application of RMM to measure particle mass and concentration for three types of graphene oxide (GO) aqueous dispersions. Using micro- and nano-suspended resonating sensors, we were able to decipher gravimetric differences between GO and graphitic materials. Our results support the urge for proper definitions and standardisations of graphene based materials, and offer a new method of characterisation for 2D material colloids in liquid suspension.